Sea Ice—Ocean Interactions in the Barents Sea Modeled at Different Resolutions - Docquier, David; Fuentes-Franco, Ramón; Koenigk, Torben; Fichefet, Thierry (Frontiers in Earth Science, 2020)
The Barents Sea is one of the most rapidly changing Arctic regions in terms of sea ice. As it is almost ice-free in summer, most recent changes in the Barents Sea have occurred in winter, with a reduction of about 50% of its March sea-ice area between 1979 and 2018. This sea-ice loss is clearly linked to an increase in the Atlantic Ocean heat transport, especially through the Barents Sea Opening, in the western part of the Barents Sea. In this study, we investigate the links between the March Barents sea-ice area and ocean heat transport at the Barents Sea Opening using seven different coupled atmosphere-ocean general circulation models, with at least two different horizontal resolutions for each model. These models follow the High Resolution Model Intercomparison Project protocol, and we focus on the historical record (1950–2014). We find that all models capture the anticorrelation between March sea-ice area and annual mean ocean heat transport in the Barents Sea. Furthermore, the use of an increased ocean resolution allows to better resolve the different ocean pathways into the Barents Sea and the Atlantic Water heat transport at the Barents Sea Opening (reduced transect). A higher ocean resolution also improves the strong water cooling at the sea-ice edge and further formation of warm intermediate Atlantic Water. However, the impact of a higher ocean resolution on the mean March Barents sea-ice area and ocean heat transport at the Barents Sea Opening (large transect) varies among models. A potential reason for a different effect of model resolution on ocean heat transport when considering a reduced or a large transect is that the Atlantic Water and Norwegian Coastal Current inflows are under-represented at lower ocean resolution. Finally, we do not find a systematic effect of resolution on the strength of the sea-ice area—ocean heat transport relationship.